Acute Aortic Dissection Mimicking STEMI in the Catheterization Laboratory: Early Recognition Is Mandatory. (10th October 2012) - Arrivi, Alessio; Tanzilli, Gaetano; Puddu, Paolo Emilio; Truscelli, Giovanni; Dominici, Marcello; Mangieri, Enrico
Abstract : Coronary malperfusion due to type A aortic dissection is a life-threatening condition where timely recognition and treatment are mandatory. A 77-year-old woman underwent an acute evolving type A aortic dissection mimicking acute myocardial infarction. Two pathophysiologic mechanisms are discussed: either thrombosis migrating from a previously treated giant aneurism of proximal left anterior descending or a local arterial complication due to left main stenting. Recognition of these occurrences in the catheterization laboratory is important to look immediately for surgery.